The Influence of Human Body Orientation on Distance Judgments - Jung, Edgard; Takahashi, Kohske; Watanabe, Katsumi; de la Rosa, Stephan; Butz, Martin V.; Bülthoff, Heinrich H.; Meilinger, Tobias (Frontiers in Psychology, 2016)
People maintain larger distances to other peoples’ front than to their back. We investigated if humans also judge another person as closer when viewing their front than their back. Participants watched animated virtual characters (avatars) and moved a virtual plane towards their location after the avatar was removed. In Experiment 1, participants judged avatars, which were facing them as closer and made quicker estimates than to avatars looking away. In Experiment 2, avatars were rotated in 30 degree steps around the vertical axis. Observers judged avatars roughly facing them (i.e., looking max. 60 degrees away) as closer than avatars roughly looking away. No particular effect was observed for avatars directly facing and also gazing at the observer. We conclude that body orientation was sufficient to generate the asymmetry. Sensitivity of the orientation effect to gaze and to interpersonal distance would have suggested involvement of social processing, but this was not observed. We discuss social and lower-level processing as potential reasons for the effect.